Thinking and Working Politically: Learning from practice. Overview to Special Issue - and McCulloch, Neil; Piron, Laure-Hélène (Development Policy Review, 2019)
Over the last 15 years, a set of ideas now referred to as “thinking and working politically” (TWP) has coalesced into a “second orthodoxy” about how to take context into account when implementing development interventions. This approach stresses the importance of obtaining a better understanding of the local context (“thinking politically”) in order to support local actors to bring about sustainable developmental change (“working politically”). However, the evidence base to justify this new approach remains thin, despite a growing number of programmes which purport to be implementing it. Officials in development agencies struggle with putting it into practice and it is unclear how TWP differs—or not—from similar approaches, such as Problem Driven Iterative Adaptation (PDIA) and Doing Development Differently (DDD). This Special Issue sheds light on what TWP means in practice by examining a set of initiatives undertaken by both development partners and government departments in Nigeria, the Occupied Palestinian Territories, China and India. This overview article outlines, in brief, each of the Special Issue's four papers and then draws out five lessons—for funders and for practitioners—from across all the papers. Our five lessons are: (1) the fundamental importance of undertaking political economy analysis (PEA) to adapt programmes to their contexts; (2) the importance of having a realistic level of ambition for interventions; (3) the need to support local ownership—not just “agreement ownership” (between a donor agency and government) or local “management ownership” of the programme, but critically “driver ownership” by generating trust with the key local actors driving change; (4) the need for a more effective set of tools for measuring results in complex programmes that attempt to achieve improvements in long-run governance; and, (5) that although the political economy of donors is often seen as a barrier to applying TWP, the articles show how much can be done with a TWP approach if the analysis takes into account the political economy of donors as well as that of the local context. We conclude with a set of operational recommendations for donors and implementors, as well as suggestions of avenues for further research.
Keywords: Adaptation; Development programmes; Political economy analysis; Reform space; thinking and working politically